Evaluasi Penggunaan Chemical Pour Point Depressant (PPD) pada Sampel Crude Oil Sumur 21 - Ali Wardhana Putra; Muhammad Sulaiman (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Crude oil with a high wax content has the potential to experience an increase in pour point, which can impede fluid flow in flow assurance. This study aims to evaluate the use of a chemical Pour Point Depressant (PPD) in lowering the pour point of crude oil samples from Well 21. The method used was a laboratory experiment involving API Gravity, BS&W, viscosity, and initial pour point testing, as well as pour point testing after adding PPD at doses of 50–350 ppm. The characterization results showed an API Gravity of 15.3°API, a viscosity of 20.25 cP, a BS&W of 50%, and an initial pour point of 26°C. The addition of PPD lowered the pour point to 21°C at a dosage of 50 ppm, 20°C at 100 ppm, 19°C at 150 ppm, 17°C at 200 ppm, 16°C at 250 ppm, and 13°C at dosages of 300–350 ppm. Based on technical and economic evaluations, the 150 ppm dose was deemed the most effective because it was able to lower the pour point below the minimum field operating temperature at a relatively low cost.